Caspase-Mediated Cleavage, IAP Binding, and Ubiquitination: Linking Three Mechanisms Crucial for Drosophila NF-kappaB Signaling. - Paquette, N.; Broemer, M.; Aggarwal, K.; Chen, L.; Husson, M.; Ertürk-Hasdemir, D.; Reichhart, J.M.; Meier, P.; Silverman, N. (Molecular Cell, 2010)
Innate immune responses are critical for the immediate protection against microbial infection. In Drosophila, infection leads to the rapid and robust production of antimicrobial peptides through two NF-kappaB signaling pathways-IMD and Toll. The IMD pathway is triggered by DAP-type peptidoglycan, common to most Gram-negative bacteria. Signaling downstream from the peptidoglycan receptors is thought to involve K63 ubiquitination and caspase-mediated cleavage, but the molecular mechanisms remain obscure. We now show that PGN stimulation causes caspase-mediated cleavage of the imd protein, exposing a highly conserved IAP-binding motif (IBM) at its neo-N terminus. A functional IBM is required for the association of cleaved IMD with the ubiquitin E3-ligase DIAP2. Through its association with DIAP2, IMD is rapidly conjugated with K63-linked polyubiquitin chains. These results mechanistically connect caspase-mediated cleavage and K63 ubiquitination in immune-induced NF-kappaB signaling.